Reproductive Health Knowledge of Adolescent in Padang: Case Study of SMA N 1 Students - Aladin Aladin (Andalas Obstetrics And Gynecology Journal, 2021)
The aim of this study is to describe the knowledge level and accuracy of reproductive health among students at SMA N 1 Padang. The study design was analytical survey with cross-sectional approach. The population were all SMA N 1 students while cluster random sampling was applied to get 267 students as respondents which represented each major (natural science or social science) and class (X, XI, and XII). The questionnaires were divided into several sections consisting the general knowledge of reproductive health, contraception, and sexually transmitted disease (STD). Result of the study showed that students in natural science major (scoring 71.9%) were having better knowledge than students in social science major (scoring 51.8%). It was also found that students in grade XII (scoring 67.7%) were getting highest result compared to students in grade XI (scoring 61.4%) and grade X (scoring 67.1%). Nevertheless, the result was not satisfying, considering that the average score of all students were only 65.6%. Therefore, guidance from parents, teachers, as well as counselling unit are crucial to help adolescent in Padang, in the context of reproductive health knowledge.